Analisis Fenomena Diglosia Pada Mahasiswa Pendidikan Bahasa Dan Sastra Indonesia Universitas Siliwangi - Hesti Nurlinda; Bintang Putri Pamungkas; Ichsan Fauzi Rachman (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research intended to describe langue often used by students, by describing the form of diglossia and describing the trigger factors. This type of research is descriptive research using a qualitative approach. The object of the research is student conversations from linguistic activities in the campus environment. Data collection uses observation, interviews and documentation methods accompanied by recording tools. The results of the research show that Siliwangi University Indonesian Language Education students use more than one language. The results showed that students used variations of T and R diglossia in their conversations, especially in the use of Sundanese and Indonesian. Diglossia found in students is caused by several factors such as bilingualism, situation, and prestige.